Analisis Yuridis Pengawasan Manifes Penumpang Untuk Mewujudkan Kelaiklautan Kapal (Studi Penelitian di Kantor Kesyahbandaran dan Otoritas Pelabuhan Khusus Batam) - Jeki Jukrisno; Ramon Nofrizal; Bachtiar Simatupang (Universitas Batanghari Jambi, 2023)
In a maritime country like Indonesia, the role of shipping in the socio-economic life of the population is very important, the sea and ships are a unity of transportation systems at sea that cannot be separated, history proves the movement of trade and distribution of population with the use of human labor, starting from rowing boats, installing sails, to being driven by machines and we arrive at the term shipping for water transportation activities at sea, To be able to create shipping conditions as expected, every voyage must prioritize seaworthy conditions. The problem in this study is how to apply passenger manifest supervision to achieve ship seaworthiness, how to regulate passenger manifest supervision to achieve ship seaworthiness, and what factors hinder passenger manifest supervision to achieve ship seaworthiness. This research uses normative techniques (legal research) with sociological and descriptive research types to collect primary data through field research. Law Number 17 of 2008 concerning Shipping, which regulates the responsibility and authority of harbour master as one of the pioneers of shipping safety supervision, as well as seaworthiness standards for ships before obtaining sailing permits. The study's conclusion is that since governments are responsible for making and enforcing laws, they are expected to create specific laws and regulations that address the authority of law enforcement organizations at sea so that they can serve as a starting point for the prosecution of maritime offenses, streamline shipping, improve inter-agency surveillance, and safeguard the jurisdiction of waters.